INTEGRATION OF MULGA MEDIA TECHNOLOGIES IN THE EDUCATIONAL PROCESS FACULTIES OF ARTS AND GRAPHICS PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS - Pereverzov, O.V. (Osvìtnìj vimìr (Online), 2022)
Possibilities of introduction in the educational program of fine on departments of pedagogical educational establishments of computer technologies for rationalization and increase to the coefficient of mastering of useful information, forming of the developed creative personality of student are examined in the article.